Antigen Presentation, Autoantigens, and Immune Regulation in Multiple Sclerosis and Other Autoimmune Diseases - Riedhammer, Christine; Weissert, Robert (Frontiers in Immunology, 2015)
Antigen presentation is in the center of the immune system, both in host defense against pathogens, but also when the system is unbalanced and autoimmune diseases like multiple sclerosis (MS) develop. It is not just by chance that a major histocompatibility complex gene is the major genetic susceptibility locus in MS; a feature that MS shares with other autoimmune diseases. The exact etiology of the disease, however, has not been fully understood yet. T cells are regarded as the major players in the disease, but most probably a complex interplay of altered central and peripheral tolerance mechanisms, T-cell and B-cell functions, characteristics of putative autoantigens, and a possible interference of environmental factors like microorganisms are at work. In this review, new data on all these different aspects of antigen presentation and their role in MS will be discussed, probable autoantigens will be summarized, and comparisons to other autoimmune diseases will be drawn.